Inheritance Justice in Substitute Heirs: A Comparative Study of Indonesia and Algeria - Kifli, Muhammad; Rouf, Abd. (Tebuireng: Journal of Islamic Studies and Society, 2026)
Substitute inheritance is a form of reform in Islamic inheritance law in Indonesia that aims to provide protection to grandchildren whose parents predecease the testator. However, its provisions continue to generate debate regarding the limits of protection that can be provided to ensure fairness in inheritance distribution. This study aims, first, to compare the provisions for substitute inheritance in Article 185 of the Compilation of Islamic Law with the tanzil mechanism in the Algerian Code de la Famille. Second, analyze the relevance of the limitation of rights in the tanzil mechanism as a normative perspective to strengthen the implementation of distributive justice in the regulation of substitute inheritance in Indonesia. This study is a normative legal study with a statutory, conceptual, and comparative legal approach. Primary, secondary, and tertiary legal materials were analyzed qualitatively using prescriptive methods. The results show that both systems provide protection to grandchildren, but through different legal constructions. Substitute inheritance in Indonesia places grandchildren as substitutes for their parents, while tanzīl in Algeria, rights are granted to grandchildren through a special mechanism that includes restrictions in the form of a maximum share limit and takes into account gifts, bequests, or other gifts received from the testator during his lifetime. This comparison shows that the tanzil arrangement provides a more comprehensive limitation mechanism in realizing proportional inheritance distribution. This research contributes by offering normative developments for the regulation of substitute inheritance in Indonesia through the adoption of the principle of proportionality in the tanzil mechanism without changing the basic character of the Islamic inheritance system in Indonesia.